Are We Moving Towards Functioning Agricultural Markets and Trade Relations?. (21st July 2016) - Brosig, Stephan; Glauben, Thomas; Levkovych, Inna; Prehn, Sören; Teuber, Ramona
Abstract: We introduce a special feature on the functioning of international agricultural markets. This feature is motivated by the increased interest in the functioning of commodity markets raised by unprecedented price turbulences since 2008, major structural changes through changed roles of emerging economies and related concerns regarding food security. We argue that the delineation of non‐functioning markets from markets that adequately adjusted to adverse framework conditions lacks theoretical foundation. We discuss the relevance of some results on institutions for agricultural markets in emerging and transition countries. A synthesis of the articles included in the special feature is provided by highlighting the selection of topics that span a topical range covering price formation on world and domestic markets, market power and trade policy modelling.